Performance analysis of databases created in virtualized and containerized environment - Zygmunt Łata; Maria Skublewska-Paszkowska (Journal of Computer Sciences Institute)
Database systems are currently implemented on different environments - containerized and virtualized. This paper aimed to compare the performance of relational databases running on these two environments. Therefore, two research hypotheses were formulated. The first hypothesis assumed that databases running on Docker containers are more efficient than those on virtual machines. The second one assumed that the Oracle is the most efficient database regardless of which environment it was run on. MySQL, PostgreSQL, Microsoft SQL Server and Oracle databases were tested. The study measured the execution times of INSERT, UPDATE, DELETE and SELECT queries. Each test was repeated 100 times. It was stated that databases running on Docker containers outperform instances running on virtual machines. Furthermore, it was found that the PostgreSQL database have a definite advantage in performance over the rest, analysed databases, which allowed the second hypothesis to be rejected.